Study of the influence of 2.5% Mg2+ insertion in the B-site of La0.8Ca0.1Pb0.1FeO3 on its structural, electrical and dielectric properties. Issue 52 (7th October 2021) - Issaoui, H.; Benali, A.; Issaoui, F.; Dhahri, E.; Costa, B. F. O.; Graca, M. P. F.; Valente, M. A.; Bouazizi, Mohamed Lamjed
Abstract : This work involves the synthesis and study of physical properties of the La0.8 Ca0.1 Pb0.1 Fe0.975 Mg0.025 O3 compound, which has been characterized by various experimental techniques, such as X-ray diffraction, SEM and complex impedance spectroscopy. Abstract : This work involves the synthesis and study of physical properties of the La0.8 Ca0.1 Pb0.1 Fe0.975 Mg0.025 O3 compound, which has been characterized by various experimental techniques, such as X-ray diffraction, SEM and complex impedance spectroscopy. The structural study showed that the La0.8 Ca0.1 Pb0.1 Fe0.975 Mg0.025 O3 compound crystallized in the orthorhombic structure with the Pnma space group. The particle size and the surface morphology of this compound have been analysed using SEM. The particle size was found to be around 120 nm and we confirmed that one particle contains more than one crystallite. Importantly, the studied compound presented a giant dielectric permittivity ( ε ′ of around 9 × 10 4 at high temperature and low frequencies). An equivalent electric circuit has been deduced from the Nyquist plots of the complex impedance parts ( Z ′′ vs. Z ′) to correctly describe the electrical behavior of the La0.8 Ca0.1 Pb0.1 Fe0.975 Mg0.025 O3 compound. The chosen circuit consists of two cells mounted in series corresponding to the grain and grain boundary contributions. The electrode contribution has been detected from the frequency dependence of the imaginary part of modulus where the activation energy of each constitution has been calculated. The relaxation process and the electrical conductivity are attributed to the same type of charge carriers characterized by similar values of the activation energy determined from loss factor tangent (tg( δ )), the imaginary part of the permittivity and the modulus spectrum.